Milestones in the Teaching of Mathematics to Children in Polish Territories from the Last Decades of the Nineteenth Century Until The End of the Twentieth Century - Domoradzki, Stanisław (Journal of Education, Technology and Computer Science, 2017)
In the talk, we will present persistent efforts to provide modern mathematical education to children aged 7–10 years in the period of the partitions and the two-decade interwar period. Partic-ular attention will be paid to the works of now-forgotten Jeske (1836–1875), Jeleńska (1885–1961), Rusiecki (1892–1956). We will also underline the commitment of university professors of mathematics to mathematical education of younger children, including Banach (1892–1945). We will refer to the modern conception of teaching mathematics to younger children, among others, to the concept of children;s mathematics developed by Gruszczyk-Kolczyńska. We will observe the metamorphosis of the role of the decimal system of counting in the mathematical education of children in Poland in the period under discussion. An expanded paper was presented by the author at the 36 International conference of History of mathematics in 2015 in Poděbrady (see Domoradzki, 2015, p. 25–44).